Strategi Pemulihan Psikologi Jemaat Pasca COVID-19 Berdasarkan Kitab Mazmur 55 - Victor Angsono Huatama; Talizaro Tafonao (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
The Covid-19 pandemic outbreak has a traumatic psychological impact on all human beings on this earth, both church members and non-believers. Psychological conditions such as mental stress, anxiety, excessive fear, social asocial (avoiding social interaction) have exist and were experienced by the congregations both during and after Covid-19. This article examines strategies that can be applied (implementable strategies) by churches, pastors, counselors, volunteers and even by congregations themselves to restore the psychological impacts with or without Covid-19 infection. The purpose of this paper is to restore the psychological effects of the congregation by minimizing or eliminating the psychological burdens from heavy to moderate, moderate to small and the small ones can be eliminated. The research method used by the author is a qualitative research method by identifying and formulating the problem and then offering solutions to these problems with the main source based on the exposition and application of the book of Psalms 55: 1-24. The author also uses library sources and literatures, journals and books to complement the research holistically in order to draw comprehensive conclusions. This study found that the recovery of the negative psychological effects of the congregation after Covid-19, both through Christian counseling and self-healing, can be done by exposing and applying the text of Psalm 55: 1-24.Keywords: Strategy, Recovery, Psychology, The Church, Covid-19, Psalm 55 AbstrakAdanya wabah pandemi Covid-19 telah memberikan dampak psikologi traumatik bagi seluruh umat manusia di muka bumi ini baik warga jemaat gereja maupun yang belum percaya. Kondisi psikologi seperti tekanan jiwa (stress), kecemasan, ketakutan yang berlebih, asosial (tidak mau bergaul) nyata ada dan dialami oleh jemaat baik selama maupun pasca Covid-19. Artikel ini mengkaji strategi-strategi yang dapat diterapkan (implementable strategies) oleh gereja, pendeta, konselor, relawan bahkan jemaat sendiri untuk memulihkan psikologi jemaat pasca Covid-19. Tujuan dari penulisan ini, untuk memberikan pemahaman kepada Jemaat dalam menghadapi berbagai problem secara psikologi khusus di masa pandemik.  Metode penulisan artikel ini adalah metode penelitian kualitatif dengan mengeksposisi Kitab Mazmur 55:1-24. Penulis juga menggunakan sumber dan literatur perpustakaan, jurnal serta buku yang melengkapi kajian dalam penulisan artikel ini.  Hasil kajian ini menemukan bahwa doa, konsistensi dan penyerahan, serta percaya kepada Allah merupakan kunci dalam menghadapi berbagai problem berdasarkan teks Mazmur sebagaimana penjelasan dalam artikel ini. Dengan demikian pemeliharaan Tuhan masih nyata dan relevan sampai saat ini.Kata Kunci:   Strategi, Pemulihan, Psikologi, Jemaat, Covid-19, Mazmur 55